Innovation, Sustainability, Development: A New Manifesto - Centre, STEPS (STEPS Centre, 2010)
Our Manifesto project publication is available in print, on CD or to v iew online. Innovation, Sustainability, Development: A New Manifesto r ecommends new ways of linking science and innovation to development fo r a more sustainable, equitable and resilient future. The multimedia v ersion, with added audio, video and background documents, is available on CD and online.